Mesenchymal stem cell and exosome-based therapy for liver diseases: can it overcome conventional therapeutic inconsistencies? - Zahid Hussain (Exploration of Digestive Diseases)
Liver inflammation, injury, and hepatic cell death are caused by external agents (viruses, bacteria, drugs, alcohol, etc.) along with the genetic susceptibility of an individual. Persistent activation of the fibrogenic response in cells leads to liver fibrosis which in turn progresses to cirrhosis and cancer. The dysregulation of the immune system generates reactive oxygen species which in turn induce necrosis of hepatocytes. This process activates hepatic stellate cells and myofibroblasts to produce a huge quantity of collagens, alpha-smooth muscle actin, and extracellular matrix deposition in liver parenchyma. Due to the multifactorial nature of this disease, conventional therapies increasingly attempted combinatorial therapy or polytherapy to target multiple mechanistic sites in order to prevent entry into further complicated irreversible stages. Despite advancements in conventional therapy, several cases aggravate fibrosis (grade 3 to 4) and cirrhosis. The inconsistency in treatment outcomes and limited organ donors for liver transplantation have led to an ever-increasing and challenging demand for alternative therapies. In this review, we analyze the mechanism and causative factors of liver diseases, conventional mode, and alternative therapeutic options. The central to liver diseases are immune dysregulation, hence bioactive agents with immunomodulatory properties should be searched and exploited to meet therapeutic needs. Mesenchymal stem cells (MSCs) with their specialized anti-inflammatory and immunomodulatory properties could be utilized as an effective alternative therapeutic candidate in treating inflammatory liver diseases. MSC-derived exosome further provides an additional immunomodulatory option that could work in tandem with MSC in a synergistic form. In this series, we have reviewed preconditioned and genetically edited MSCs to augment homing, proliferation, and differentiation. Importantly, all the clinical challenges should be noted and addressed before stem cell cytotherapy should be considered safe and effective for patients with liver diseases. Published literature indicated that MSC therapy has the potential to substitute conventional options in the treatment of high-grade fibrosis and cirrhosis.